Future Trends in Biotechnology Patents: Impact of Nano-Biomedicine and Artificial Intelligence on the Patent Landscape - R. Tjandrawinata, Raymond; Soelistyo Budi, Henry (Journal of Law, Politic and Humanities, 2025)
The development of nano-biomedicine and artificial intelligence (AI) technologies are changing the biotechnology landscape and the global patent system. Both technologies are advancing innovation in sectors such as oncology, genetic diseases, and vaccinology, while posing new challenges in the intellectual property legal framework. This article analyzes the specific sectors most affected by these technologies, discusses regulatory efforts in specific jurisdictions, as well as highlights patent-related case studies of major companies. Additionally, an analysis of the risks and opportunities for collaboration between various parties is outlined to demonstrate the need for regulatory reform to support global innovation. The article also provides strategic recommendations for policymakers as well as long-term projections on the impact of this technology on the patent system in the next 20-30 years.